1985
DOI: 10.1073/pnas.82.21.7256
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Ca2+ release channels with ryanodine in junctional terminal cisternae of sarcoplasmic reticulum of fast skeletal muscle.

Abstract: The mechanism of Ca2' release from sarcoplasmic reticulum, which triggers contraction in skeletal muscle, remains the key unresolved problem in excitation-contraction coupling. Recently, we have described the isolation of purified fractions referable to terminal and longitudinal cisternae of sarcoplasmic reticulum. Junctional terminal cisternae are distinct in that they have a low net energized Ca2+ loading, which can be enhanced 5-fold or more by addition of ruthenium red. The loading rate, normalized for cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
195
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(203 citation statements)
references
References 27 publications
6
195
1
1
Order By: Relevance
“…If as suggested, ryanodine is a Ca 2+ release channelspecific marker [3,6,19,20] then it should affect the Ca 2+ permeability of the liver microsomes. This was tested by determining the Ca z+ permeability of vesicles passively loaded with 45CaZ+ in the presence and absence of ryanodine.…”
Section: Membrane Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…If as suggested, ryanodine is a Ca 2+ release channelspecific marker [3,6,19,20] then it should affect the Ca 2+ permeability of the liver microsomes. This was tested by determining the Ca z+ permeability of vesicles passively loaded with 45CaZ+ in the presence and absence of ryanodine.…”
Section: Membrane Preparationsmentioning
confidence: 99%
“…These effects are due to the interaction of ryanodine with the SR, thereby modulating the Ca 2÷ release activity of this membrane [2,3]. Recent studies identified morphologically the purified ryanodine receptor with the 'foot' structure [4] and with the junctional Ca 2÷ release channel [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Ryanodine receptor, which is located on the terminal cisternae of SR (FLEISCHER et al, 1985), has been purified (a single polypeptide of Mr 360,000) and shown to display Ca2 + channel activity with characteristics similar to the Ca2 +-induced Ca2 + release channel (FLEISCHER et al, 1985;HYMEL et al, 1988;LAI et al, 1988). Rapid Ca2 + release produced by either binding of heavy metals to or oxidation of sulfhydryl group on the SR membrane is strikingly similar to Ca2 +-induced Ca2 + release (SALAMA and ABRAMSON, 1984;TRIMM et al, 1986;MOUTIN and DUPONT, 1988;STUART and ABRAMSON, 1988;TATSUMI et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The following studies were aimed at defining which of the many pathways of caffeine action is involved. (Slivka and Insel, 1987;Gronich et al, 1990;Nakamura et al, 1991;Weiss and Insel, 1991), and millimolar concentrations of caffeine may increase [Ca 2 + ] i c o n c e n t r a t i o n both in muscular (Fleischer et al, 1985;Campbell et al, 1987;Iino et al, 1988) and non-muscular cells (Lipscombe et al ., 1988;Burgoyne et al ., 1989;Hernandez-Cruz et al, 1990;Malgaroli et al, 1990;Zacchetti et al, 1991). Caffeine mobilizes cellular Ca 2+ from intracellular stores by activating Ca 2 + channels that are sensitive to ryanodine.…”
Section: Caffeine Increases the Rate Of Incorporation Of [ 14 C]cholimentioning
confidence: 99%
“…It is well known that in a variety of cell types such as muscular cells (Fleischer et al, 1985;Campbell et al , 1987;Iino et al, 1988), neurons (Lipscombe et al, 1988;Hernandez-Cruz et al, 1990;Zacchetti et al, 1991), endocrine cells (Burgoyne et al, 1989;Malgaroli et al, 1990) and the pancreatic acinar cells (Wakui et al, 1990), caffeine increases the intracellular free calcium ([Ca 2+ ] i ) level through ryanodine, a neutral plant alkaloid, -sensitive or -insensitive Ca 2 + channel located in intracellular calcium stores. However, there is no informations about the action of caffeine and ryanodine on the cellular calcium change in renal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%